On the Right Track to Treat Movement Disorders: Promising Therapeutic Approaches for Parkinson’s and Huntington’s Disease - Troncoso-Escudero, Paulina; Sepulveda, Denisse; Pérez-Arancibia, Rodrigo; Parra, Alejandra V.; Arcos, Javiera; Grunenwald, Felipe; Vidal, Rene L. (Frontiers in Aging Neuroscience, 2020)
Movement disorders are neurological conditions in which patients manifest a diverse range of movement impairments. Distinct structures within the basal ganglia of the brain, an area involved in movement regulation, are differentially affected for every disease. Among the most studied movement disorder conditions are Parkinson’s and Huntington’s disease, in which the deregulation of the movement circuitry due to the loss of specific neuronal populations in basal ganglia is the underlying cause of motor symptoms. These symptoms are due to the loss principally of dopaminergic neurons of the substantia nigra par compacta and the GABAergic neurons of the striatum in Parkinson’s disease and Huntington’s disease, respectively. Although these diseases were described in the 19th century, no effective treatment can slow down, reverse, or stop disease progression. Available pharmacological therapies have been focused on prevent or alleviate motor symptoms to improve the quality of life of patients, but these drugs are not able to mitigate the progressive neurodegeneration. Currently, considerable therapeutic advances have been achieved seeking a more efficacious and durable therapeutic effect. Here, we will focus on the new advances of several therapeutic approaches for Parkinson’s and Huntington’s disease, starting with the available pharmacological treatments to alleviate the motor symptoms in both diseases. Then, we describe therapeutic strategies that aim to restore specific neuronal populations or their activity. Among the discussed strategies, the use of neurotrophic factors and genetic approaches to prevent the neuronal loss in these diseases will be described. We will highlight strategies that have been evaluated in both Parkinson’s and Huntington’s patients, and also the ones with strong preclinical evidence. These current therapeutic techniques represent the most promising tools for the safe treatment of both diseases, specifically those aimed to avoid neuronal loss during disease progression.